MANAJEMEN PEMBELAJARAN EKONOMI DIMASA PANDEMI COVID-19 PADA GURU EKONOMI KOTA SINTANG - Sarini, Sabina; Aminuyati, Aminuyati; Basri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
abstractThis research is entitled Management of Economic Learning during the Covid-19Pandemic for Economic Teachers in Sintang City. This study aims to determinehow planning, organizing, actuating, and evaluating on economic learning inSMA Sintang City? This research approach uses a qualitative approach, theresearch form is descriptive, and the informants in this study are 5economicteachers, 65 students, 2 principals of SMA Negeri Sintang City. 1 head ofcurriculum. The techniques used in this research data collection are interview,observation, and documentation. The results of this study indicate that what theschool is currently doing is using Virtual Learning such as whatsapp Group,Google Form, quizizz, audio Visual, power point,and classroom to facilitate thelearning process of the implementatiton function is to carry out thepredetermined plan. Economics teachers also evaluate students. Properevaluation is an effort to form decisions about the level of student learningoutcomes in accordance with learning objectives.Keywords: Management, Economics Learning, Pandemic period, Economics Teacher.